The Frontal Sinus - Kountakis, Stilianos E.; Senior, Brent A.; Draf, Wolfgang (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This is the only book dedicated solely to frontal sinus disorders. It is a richly illustrated and comprehensive mine of information on the anatomy and management of these disorders. This updated second edition offers much new information. Additional topics include balloon dilation, frontal surgery as part of skull base surgery, and advances in endoscopic techniques and tools that have occurred since 2004 and have made open osteoplastic procedures almost obsolete. The anatomy and surgery of the supraorbital ethmoid cell and its significance in the pathology of frontal sinus disease are also covered. Throughout the book, particularly important areas of text are highlighted and core messages, emphasized. Videos of described procedures are available online.